THE TURJAWALI UNIT'S CONTRIBUTION TO THE POLICE STATION OF PURWAKARTA'S EFFORT TO PREVENT TRAFFIC ACCIDENTS - Muhammad Arif Rahman; Abdul Muta'ali; Surya Nita (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
A high number of accidents in Purwakarta Regency can be traced back to the region's growing population and accompanying rise in traffic density, both of which are effects of the widespread availability of personal motor vehicles and the slow pace at which the region's transportation infrastructure has been able to catch up with that growth. Article 226 of Law 22 of 2009, which regulates traffic and transportation, includes provisions for preventing accidents. The investigation was carried out at the Purwakarta Police, and articles were published that were of a high quality. The articles focused on the measures undertaken by the Turjawali Traffic Unit of the Purwakarta Police to prevent the occurrence of vehicle accidents (Poles Purwakarta). According to research findings, the Purwakarta Police Department has taken three strategies to limiting the number of traffic-related deaths and injuries among young people: (1) premptive steps, such as implementing a national traffic safety program and a child-friendly police and law enforcement force; (2) preventive measures, like holding an annual traffic safety awareness event called Turjawali; and (3) repressive measures, like responding to accidents after they have already occurred.